Shaking table tests of stone masonry buildings - Mendes, N. (2010)
This paper presents the main results of experimental tests concerning the reduction of the seismic vulnerability of stone masonry buildings with flexible floors. The tests were performed in the LNEC 3D shaking table by imposing artificial accelerograms in two horizontal uncorrelated orthogonal directions, triggering in-plane and out-of-plane response of two tested mock-ups; one in original condition and another repaired. The preliminary results show that adopted measures are efficient, allowing to improve the seismic performance of this building typology.